General approach to simple algorithms for 2-D positioning techniques in cellular networks - Doukhnitch, E.; Salamah, M. (Elsevier, 2008)
Finding the location of an object is one of the important features of autonomous and the 3G/4G wireless communication systems. Many valuable location based services can be enabled by this feature. Position estimation from Time of Arrival (TOA), Time Difference of Arrival (TDOA), and Angle of Arrival (AOA) measurements are the commonly used techniques. These approaches use the location parameters received from different sources, and they are based on intersections of circles, hyperbolas, and lines, respectively. The location is determined using standard complex computation methods that are usually implemented in software. In this paper, we propose a general approach to design new hardware-oriented algorithms that use only simple add and shift operations in the computation and therefore can be easily implemented in hardware or firmware. In addition to their implementation simplicity, the proposed algorithms outperform the conventional ones in terms of the required number of operations for a specific accuracy level. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: positioning; angle of arrival; time of arrival; hardware algorithms; wireless networks